Enhanced Performance of Epoxy Resin-Polyimide Hybrid Composites with Aminated Carbon Nanofibers Filler - Saraswati, Teguh Endah; Saputri, Dini Deviana; Raharjo, Wijang Wisnu (Science and Technology Indonesia, 2025)
Incorporating epoxy resin (ER) and polyimide (PI) with supporting filler will exhibit composites with exceptional mechanical, thermal, and electromagnetic shielding properties. This research investigates the preparation of aminated carbon nanofiber (CNF) as a filler in epoxy resin-polyimide hybrid composites. The preparation of the CNF filler was initially done by the purification process through dissolution in toluene and vacuum annealing at 800°C for 3 hours. The amine modification of CNF was done by reacting CNF with ethylenediamine, sodium nitrite, and sulfuric acid. The aminated CNF was then mixed with polyimide precursor (oxydianiline and pyromellitic dianhydride), becoming poly(amic acid)-filler. The last step was combining poly(amic acid)-filler with epoxy resin diglycidyl ether bisphenol A and polyaminoamide as hardener. The Scanning Electron Microscope (SEM) and Transmission Electron Microscopy (TEM) images of CNF showed the overlapped bundle fibers with the average fiber diameter around 100-120 nm. The successful amine modification was analyzed through Fourier-Transform Infrared (FTIR) analysis by the functional group emergence of C–N (∼1153 cm-1), N H (3737 cm-1), primary amine N–H (1534 cm-1), and better dispersion in water. The aminated filler shows a better distribution in the polymer matrices observed through macroscopic images and a higher hardness value. The FTIR of composites shows the increasing intensity in the N–H, C O amide, and C–H functional groups, indicating the highly covalent bonds between polymers and the aminated CNF filler. The TGA graph shows the recognizable termination of the polyimide and epoxy resin matrices as major components in the composite. The ER-PI composites with aminated CNF filler show improved mechanical properties in the hardness, tensile properties, and electromagnetic interference (EMI) shielding efficiency by around three-fold higher than composites with unmodified CNF filler.